Auto-Ignition and Reaction Front Dynamics in Mixtures With Temperature and Concentration Stratification - Tao, Mingyuan; Yang, Qi; Lynch, Patrick; Zhao, Peng (Frontiers in Mechanical Engineering, 2020)
In-cylinder thermal and concentration stratification is omnipresent in the operation of internal combustion engines, especially for various types of direct injection engines. Meanwhile, mixture stratification and ϕ-sensitivity is frequently adopted in advanced compression ignition strategies to modulate heat release profile and control combustion phasing, such as homogeneous charge compression ignition (HCCI) with partial fuel stratification (PFS), and premixed charge compression ignition (PCCI). Hence, ignition and combustion mode evolution in a stratified charge are of substantial significance in the understanding and prediction of combustion in advanced compression ignition engines. To probe complex combustion in a stratified charge, we have performed one-dimensional direct numerical simulations with detailed chemistry and transport, using a recently developed open source reacting flow CFD platform based on OpenFOAM. N-heptane is adopted in this work as a typical fuel exhibiting low temperature chemistry. Temperature and equivalence ratio gradients are varied among the simulations to observe ignition and the subsequent combustion development. Three stages of heat release are identified, including the low temperature chemistry chain branching, H2O2 chain branching and CO oxidation, consistent with the recent ignition experiment for lean n-heptane air mixture in a rapid compression machine (RCM). Reaction fronts induced by these oxidation stages are found to be unaffected by diffusion process and exhibit unique propagation features. The results provide useful guidance to the understanding of combustion in a stratified charge and shed light on the development of novel low temperature combustion strategy for advanced compression ignition engines.